GIS-Based Coverage Analysis of Public Bus Services in Yangon City, Myanmar - Khin, May Thu Zar; Kyaw, Nyan Myint; Aye, Moe Thet Thet (The Indonesian Journal of Computer Science, 2026)
Public bus transport is the dominant travel mode in Yangon, serving millions of daily commuters and playing a vital role in urban mobility. This study presents a GIS-based coverage analysis of public bus services in Yangon City to evaluate spatial accessibility and identify service gaps within the transit network. Service effectiveness is assessed using coverage indicators, including service area buffers, population coverage ratios, and accessibility indices. The results show that central townships, such as South Okkalapa Township, Yankin Township, and Thaketa Township, achieve high coverage levels exceeding 80%, while peripheral areas, including Mingalardon Township and Dagon Myothit Township, remain below 40%. Heat map analysis highlights dense coverage in the central business district and surrounding areas, contrasted with limited accessibility in outer regions such as Hlaingtharyar Township. Key service gaps are also identified along major corridors like Parami Road and Bayint Naung Road. The study reveals significant spatial inequalities in transit accessibility and provides a data-driven basis for improving sustainable urban transport planning.